2015
DOI: 10.3892/ol.2015.3997
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells promote tumor angiogenesis via the action of transforming growth factor β1

Abstract: Abstract. Mesenchymal stem cells (MSCs) may influence the growth and metastasis of various human malignancies, including hepatocellular carcinoma (HCC). Therefore, the underlying mechanisms via which MSCs are able to affect malignancies require investigation. In the present study, the potential role of MSC in the angiogenesis of HCC was investigated. A total of 17 nude mouse models exhibiting human HCC were used to evaluate the effects of MSC on angiogenesis. A total of 8 mice were injected with human MSCs via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…For instance, MSCs recruited in breast and prostate tumors were found to increase the expression of angiogenic factors, including TGFβ, VEGF and Interleukin 6, which contribute to tumor growth and vascularization (Zhang et al, 2013). Similarly, a correlation between increased expression of TGFβ1 and higher microvessel density was observed in hepatocellular carcinomas of mice receiving intravenous injections of human MSCs (Li et al, 2016). This study further supported that MSCs may enhance tumor angiogenesis via TGFβ.…”
Section: Pro-tumor Activitysupporting
confidence: 57%
See 1 more Smart Citation
“…For instance, MSCs recruited in breast and prostate tumors were found to increase the expression of angiogenic factors, including TGFβ, VEGF and Interleukin 6, which contribute to tumor growth and vascularization (Zhang et al, 2013). Similarly, a correlation between increased expression of TGFβ1 and higher microvessel density was observed in hepatocellular carcinomas of mice receiving intravenous injections of human MSCs (Li et al, 2016). This study further supported that MSCs may enhance tumor angiogenesis via TGFβ.…”
Section: Pro-tumor Activitysupporting
confidence: 57%
“…In contrast to investigations describing the pro-angiogenic effect of MSCs (Zhang et al, 2013;Li et al, 2016), the antitumor activity of MSCs via inhibition of tumor angiogenesis has also been documented. A study reported that bone marrow MSCs restrict vascular growth in Gli36 glioma xenograft through downregulation of the PDGF/PDGFR axis (Ho et al, 2013).…”
Section: Anti-tumor Activitymentioning
confidence: 99%
“…Angiogenesis is considered as a critical step for cancer development and progression. MSCs can favor the formation of tumor blood vessels and thus promote tumor growth and metastasis ( 26 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, MSCs are known to be associated with a higher degree of metastasis development. [80][81][82] When MSCs are co-injected with human breast cancer cells such as MCF-7, MDA MB-231, and MDA MB-435, enhanced tumor growth and lung metastases are observed. 83 Production of CCL5 from MSCs that are stimulated by breast tumor cells promotes breast cancer metastasis.…”
Section: Homing Of Mesenchymal Stem Cells To Cancer Cells Is Acknowlementioning
confidence: 99%
“…Furthermore, TGF-β1 secreted by MSCs suppresses leukocytes proliferation, contributing to the tumor progression. 82 Due to the integrated tumor suppression and progression effects of MSCs, numerous factors including the types of tumor, heterogeneity, tumor microenvironment, and MSC source need to be thoroughly considered before clinical applications.…”
Section: Homing Of Mesenchymal Stem Cells To Cancer Cells Is Acknowlementioning
confidence: 99%